Assessment of Infection Control Practices Among Caregivers of Daycare Centers - Ajmal, Mehwash; Iman, Hira; Mushtaq, Naila; Sharif, Nasreen; Ajmal, Sehrish (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to assess infection control practices among caregivers in daycare centers across Punjab, Pakistan, to identify gaps and recommend improvements for reducing disease transmission. Methods: A cross-sectional study was conducted in private, public, and NGO-run daycare centers in Lahore, Islamabad, and Rawalpindi. Data were collected from 150 caregivers using a structured questionnaire divided into demographic, hygiene practices, and environmental factors. Observational data on infection control practices were also recorded. The questionnaire included a 5-point Likert scale for hygiene assessments, while immunization and child health data were self-reported. Descriptive and inferential statistics were analyzed using SPSS version 25, with p-values <0.05 considered significant. Ethical approval was obtained, and participant confidentiality was maintained per the Declaration of Helsinki. Results: Female caregivers constituted 71.3%, with a mean age of 39.91 years (SD = 11.75). Adequate hygiene facilities were reported in 72.7% of centers (p=0.012*), and regular sanitation practices were maintained in 83.3% (p=0.002**). Hand hygiene scored a mean of 3.04 (SD = 1.12), while PPE usage was 2.98 (SD = 1.10). Immunization was complete for 86.0% of children, while illness episodes averaged 2.12 (SD = 1.09, p=0.013*). Conclusion: Significant gaps in infection control practices necessitate regular training, facility improvements, and policy interventions to enhance child health and safety in daycare centers.